Antihypertensive effect of BS 100-141, a new central acting antihypertensive agent - Somchart Lochaya (2018)
A double-blind comparison between BS 100-141 and placebo in 36 hypertensive patients of Thai or Thai-Chinese origin revealed that the preparation lowers the elevated blood pressure within the first week of treatment in most patients. The drug was relatively well tolerated and caused mild side effects only. After a sudden discontinuation of the drug, the blood pressure in four of the 19 patients increased within a few days to pretreatment values or slightly above. The occurrence of rebound hypertension cannot be excluded. Interruption of treatment, therefore, should be made gradually. © 1980.